THE ANTHROPOMETRY RELATIONSHIP LONG BONE TO HEIGHT OF BATAK TOBA TRIBE STUDENT IN BEKASI CITY - Ambarita, Ezra Oktavia; Setyawati, Iriani; Yulihastuti, Dwi Ariani (SIMBIOSIS, 2022)
Forensic anthropology is the application of a specific branch of biological anthropology based on human bones and anatomy. Anthropometry is a method of measuring body parts. Height measurement is a forensic anthropological parameter that helps build a person's biological profile. Height can be determined by the size of the long bones including the humerus, radius, ulna, femur, tibia, and fibula. This research on height was carried out on Batak Toba students. This study aims to determine the anthropometric relationship of long bone length to the height of Batak Toba students in the city of Bekasi. This research is an analytic observational study with a cross sectional approach. This research was conducted in the city of Bekasi with the research subjects totaling 60 students consisting of 30 men and 30 women with an age range of 18-22 years from the Toba Batak tribe who did not have bone disorders. Samples were taken by purposive sampling technique. Data analysis was performed by Pearson Correlation (r) test. The parameters analyzed in this study were length of humerus, radius, ulna, femur, tibia, fibula, height, sitting height, weight, and body mass index. The results of the Pearson Correlation test analysis (r) showed that there is a significant relationship between the length of the humerus, radius, ulna, femur, tibia, fibula and sitting height with a strong to perfect correlation, while the relationship between body mass index and height there is no significant difference and there is no correlation to Batak Toba students in the city of Bekasi. Keywords: height, long bones, anthropometry, Batak Toba